IL-12 drives the expression of the inhibitory receptor NKG2A on human tumor-reactive CD8 T cells - Olivier Fesneau; Kimberly A. Samson; Wesley Rosales; Bretton Jones; Tarsem Moudgil; Bernard A. Fox; Venkatesh Rajamanickam; Thomas Duhen (Nature Communications)
Abstract Blockade of NKG2A/HLA-E interaction is a promising strategy to unleash the anti-tumor response. Yet the role of NKG2A+ CD8 T cells in the anti-tumor response and the regulation of NKG2A expression on human tumor-infiltrating T cells are still poorly understood. Here, by performing CITE-seq on T cells derived from head and neck squamous cell carcinoma and colorectal cancer, we show that NKG2A expression is induced on CD8 T cells differentiating into cytotoxic, CD39+CD103+ double positive (DP) cells, a phenotype associated with tumor-reactive T cells. This developmental trajectory leads to TCR repertoire overlap between the NKG2A– and NKG2A+ DP CD8 T cells, suggesting shared antigen specificities. Mechanistically, IL-12 is essential for the expression of NKG2A on CD8 T cells in a CD40/CD40L- dependent manner, in conjunction with TCR stimulation. Our study thus reveals that NKG2A is induced by IL-12 on human tumor-reactive CD8 T cells exposed to a TGF-β-rich environment, highlighting an underappreciated immuno-regulatory feedback loop dependent on IL-12 stimulation.